Genetic Characterization of Antibiotic Resistant Enterobacteriaceae Isolates From Bovine Animals and the Environment in Nigeria - Jesumirhewe, Christiana; Springer, Burkhard; Allerberger, Franz; Ruppitsch, Werner (Frontiers in Microbiology, 2022)
There is a link between antibiotic resistance in humans, livestock and the environment. This study was carried out to characterize antibiotic resistant bovine and environmental Enterobacteriaceae isolates from Edo state, Nigeria. A total of 109 consecutive isolates of Enterobacteriaceae were isolated from March-May 2015 from 150 fecal samples of healthy bovine animals from three farms at slaughter in Edo state Nigeria. Similarly, 43 Enterobacteriaceae isolates were also obtained from a total of 100 environmental samples from different sources. Isolates were recovered and identified from samples using standard microbiological techniques. Recovered isolates were pre-identified by the Microbact Gram-Negative identification system and confirmed with Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry and ribosomal multilocus sequence typing (rMLST). Antibiotic susceptibility testing was carried out by Kirby-Bauer method for 14 antibiotics. Whole genome sequencing (WGS) was carried out for isolate characterization and identification of resistance determinants. Out of 109 animal and 43 environmental Enterobacteriaceae isolates, 18(17%) and 8(19%) isolates based on selection criteria showed antibiotic resistance and were further investigated by whole genome sequencing (WGS). Resistance genes were detected in all (100%) of the resistant bovine and environmental Enterobacteriaceae isolates. The resistance determinants included β-lactamase genes, aminoglycoside modifying enzymes, qnr genes, sulphonamide, tetracycline and trimethoprim resistance genes, respectively. Out of the 18 and 8 resistant animal and environmental isolates 3(17%) and 2(25%) were multidrug resistant (MDR) and had resistance determinants which included efflux genes, regulatory systems modulating antibiotic efflux and antibiotic target alteration gene. Our study shows the dissemination of antibiotic resistance especially MDR strains among Nigerian bovine and environmental Enterobacteriaceae isolates. The presence of these resistant strains in animals and the environment constitute a serious health concern indicated by the difficult treatment options of the infections caused by these organisms. To the best of our knowledge we report the first detailed genomic characterization of antibiotic resistance in bovine and environmental Enterobacteriaceae isolates for Nigeria.